Cytotoxic Compounds Derived from Marine Algicolous and Spongicolous Endophytic Fungi: A Review (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Endophytes have gained particular interest in the search of potential pharmaceutical candidates for a long time due to their diversity, species richness and bioprospecting nature. They generally produce the essential metabolites for their expansion inside the plant which is involved in various biotransformation processes of utilizing host nutrients and cell components to continue microbial growth, sustenance, and reproduction. In above processes, they produce a huge amount of both structurally and functionally diverse secondary metabolites for maintaining an effective symbiosis with hosts. These compounds are proven to have significant bioactive properties like antibacterial, antifungal, antiviral, anti-inflammatory, antioxidants, antitumor activities. Despite the proven significance, a little is exploited so far about endophytes. Particularly marine fungal endophytes which are the centre of attention in this review have gained much less importance. Due to unique environmental feature, fungal endophytes derived from marine environment offer vast diversity in different bioactive secondary metabolites. This review has focused on algicolous endophytes and bioactive secondary metabolites discovered during the last two decades. Particular importance has been given to cytotoxic and antimicrobial metabolites. Due to intensive studies during last several years, an extensive number of publications are now available on cytotoxic compounds derived from endophytic fungi of marine algicolous and spongicolous origin that have been summarized in this review.Dhaka Univ. J. Pharm. Sci. 20(2): 247-265, 2021 (December)